Can Digital Financial Inclusion Narrow the Urban-rural Income Disparity in Central Region of China? - Liu, Jing; Puah, Chin-Hong; Arip, Mohammad Affendy; Jong, Meng-Chang (Business and Economic Research, 2024)
The purpose of this study is to investigate whether digital financial inclusion (DFI) can narrow the urban-countryside income disparity in central district of China. This study conducts an empirical analysis using the Digital Financial Inclusion Index and relevant income data from the central district of China for the period of 2011-2020. The research found that the digital credit level of DFI can significantly narrow the income disparity in the central district, but the depth of DFI usage has no significant impact on income level convergence in this area. Conversely, the total index, coverage breadth, digitization level, payment level, and insurance level of DFI can widen the income disparity in the central district. Based on these results, this paper proposes policy recommendations for narrowing the urban-countryside income disparity in this region through the evolution of DFI, which can also serve as a reference for other regions in China.